Un enigma no resuelto en dos frescos del Beato Angélico (Teología, 2020)
The author of this article, Cardinal Jorge Mejía, presents us an interesting essay abouttwo frescoes painted by Fra Angelico (c. 1395 – February 18, 1455) that of Saint Sebastianand Saint Lawrence, deacons and martyrs in the Niccoline Chapel of the Vatican Palace. After describing these frescoes, he interrogates the rite represented in them, that is, the deaconal ordination with the simbols of the priestly ordination. Cardinal Mejia offers three posible solutions to the problem.
Keywords: Fra Angelico; Religious Art; Deacons; Ministries